Pengaruh Kesadaran Wajib Pajak, Tarif Pajak dan Sanksi Pajak Terhadap Kepuasan Wajib Pajak Tanah dan Bangunan - Rahayu Mardikaningsih; Utami Puji Lestari (Forum Kerjasama Pendidikan Tinggi (FKPT), 2022)
Taxes are a source of funding for a country. The development of a country is partly financed by taxes paid by taxpayers. High tax payments have an impact on the progress of a country. For developing countries, tax awareness is still too low. Tax payments are still not made every year even though tax rates have been determined proportionally and equitably. In addition, tax sanctions that are not given significantly cause taxpayers not to pay taxes. Periodic tax payments in accordance with applicable regulations can occur if taxpayers are satisfied with the tax system and rules. The research topic taken is the Effect of Taxpayer Awareness, Tax rates and Tax Sanctions on Land and Building Taxpayer Satisfaction. The population in this study is also limited because it only focuses on Surabaya city residents who are required to pay land and building tax. The number of samples calculated is 100 residents as taxpayers with accidental sampling technique. The questionnaire will be used as a research instrument. Multiple linear regression model is the model for data analysis in this study. Based on the variables of taxpayer awareness, tax rates and tax sanctions, the result is a significant effect on the taxpayer satisfaction variable.